Role of lactoferrin in osteopenia and osteoporosis - Li, Deming; Gao, Maofeng; Li, Meng; Zhao, Huan; Zhou, Xichao; Gu, Qiaoli; Yang, Huilin; Shi, Qin (Frontiers in Nutrition, 2025)
Osteopenia and osteoporosis (OP) are serious public health concerns that impose substantial health and economic burdens on the global population. Lactoferrin (Lf) is a natural iron-binding glycoprotein that exhibits numerous biological functions. This review summarized the role of circulating Lf and related biomarkers in maintaining bone health. Lf may protect against OP through various mechanisms, including the osteoprotegerin/receptor activator of nuclear factor κB ligand/receptor activator of nuclear factor κB, bone morphogenetic protein signaling pathway, liver–bone axis, insulin-like growth factor 1 signaling pathway, autophagy, and gut microbiota. Moreover, the peptides derived from Lf and Lf-based nanoformulations or biomaterials show potential in preventing OP. Overall, this review supports the potential application of Lf for OP.